Sosialisasi Perlindungan Hukum bagi Guru dalam Menjalankan Tugasnya di Kota Bandar Lampung - Anwar, Mashuril; Lilyana, Besti; Zatika, Dinda Anna; Yuniwati (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2024)
The teaching profession is a noble and honorable field of work (officium nobile). However, nowadays, various legal cases have been found that teachers experience due to carrying out their duties in the education process. This community service activity aims to provide teachers with an understanding of legal protection for teachers in carrying out their responsibilities as educators. This community service activity is carried out using the Participatory Action Research (PAR) approach method which is oriented towards empowering teachers regarding legal protection issues in carrying out their duties. The results of community service show that teachers are educators who carry out their duties and obligations professionally. However, there is a conflict between enforcing discipline on students and Law Number 35 of 2014 concerning Child Protection. This legal counseling helps teachers understand the common thread between discipline and crime.